Erratum: Constraints on the dark matter neutralinos from the radio emissions of galaxy clusters - Kiew, C.Y.; Hwang, C.Y.; Abidin, Z.Z. (Oxford University Press, 2017)
By assuming the dark matter to be composed of neutralinos, we used the detection of upper limit on diffuse radio emission in a sample of galaxy clusters to put constraint on the properties of neutralinos. We showed the upper limit constraint on 〈σv〉–mχ space with neutralino annihilation through bb¯ and μ+μ− channels. The best constraint is from the galaxy clusters A2199 and A1367. We showed the uncertainty due to the density profile and cluster magnetic field. The largest uncertainty comes from the uncertainty in dark matter spatial distribution. We also investigated the constraints on minimal Supergravity (mSUGRA) and minimal supersymmetric standard model (MSSM) parameter space by scanning the parameters using the darksusy package. By using the current radio observation, we managed to exclude 40 combinations of mSUGRA parameters. On the other hand, 573 combinations of MSSM parameters can be excluded by current observation.